IDDF2018-ABS-0218 Efficacy of faecal microbiota therapy in patients with steroid dependent active ulcerative colitis. (June 2018) - Mahajan, Ramit; Midha, Vandana; Mehta, Varun; Singh, Arshdeep; Khattar, Husanpreet; Gupta, Yogesh; Narang, Vikram; Sood, Ajit
Abstract : Background: Faecal microbiota transplantation (FMT) has been shown to be effective in active ulcerative colitis (UC) by targeting gut dysbiosis. We assessed the role of FMT in steroid-dependent UC patients. Methods: In this trial, patients with steroid-dependent active UC were treated with FMT using random unrelated donors, by the colonoscopic approach, at weeks 0, 2, 6, 10, 14, 18 and 22. Patients with steroid-dependent UC treated who were treated without FMT in past, with azathioprine as a steroid-sparing agent were taken as historical controls. The primary outcome was the achievement of steroid-free clinical remission (Mayo score=30% and ≥3 points compared to baseline) and endoscopic remission (Mayo score 0 or 1). 16 s rRNA gene sequencing was done for analysing changes in microbial composition after FMT. Results: Between September 2015 – September 2017, 41 patients with steroid-dependent UC underwent FMT, 33 completed seven sessions over 22 weeks while 8 discontinued treatment (non-response: 5, lost to follow up: 2, fear of side effects: 1) (figure 1). At week 22, the primary endpoint (steroid-free clinical remission) was achieved in 46.3% (19/41) patients treated with FMT compared to 26.3% (10/38) in historical controls treated with azathioprine (p=0.065). Clinical response (31/41, 75.6%) and endoscopic remission (26/41, 63.4%) with FMT were significantly higher than controls (55.3% and 39.5% respectively, p=0.005) (IDDF2018-ABS-0218 Figure 2). Adverse events necessitating discontinuation were noted in 3/38 (7.89%) controls treated with azathioprine, but not with FMT. Conclusions: A multi-session FMT by a colonoscopic route is a promising therapeutic option for steroid-dependent UC patients, as it induces clinical remission and withdrawal of steroids in 46.3% and 75.6% patients respectively.